Komunikasi Imperatif Pada Bahasa Endorsment Selebgram Tasya Octav - Khamidah, Cholidatul (Universitas Nusantara PGRI Kediri, 2021)
The problem in this study is what kind of imperative communication is in the language used by the Tasya Octav celebgram. The purpose of this research journal is to describe the types of imperative sentences and imperative communication tendencies used in Tasya Octav's celebgram language. This study used descriptive qualitative method. This research is a library research. The data of this research is the speech spoken by the celebrity Tasya Octav on the uploaded endorsement video. The data source of this research refers to the transcript of the endorsement video speech on the insta story of the Instagram account of Tasya Octav's Instagram account. The data collection in this research is listening and transcripts. Based on the results of the discussion, it can be concluded that in the endorsement language, Tasya Octav more often uses the imperative sentence of giving permission.